Pemikiran Pendidikan Al-Ghazali: Studi Pemikiran Pendidikan Al-Ghazali dalam Kitab Ayyuha al-Walad - Mukit, Abdul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
One of the greatest educational problems worldwide, and particularly in this country, is the moral crisis. Morality is the foundation of education; regardless of its progress and development, education cannot be accomplished without ethics. Recognizing the urgency of addressing this issue, scholars and thinkers have proposed solutions grounded in moral principles, among them the eminent scholar Abū Ḥāmid al-Ghazālī, widely known as Ḥujjat al-Islām. He devoted significant attention to ethics, as evidenced in his writings, especially in Iḥyāʾ ʿUlūm al-Dīn. This study focuses on one of his notable works, Ayyuhā al-Walad, to uncover his educational thought and its practical application. The research problem is defined as follows: What is al-Ghazālī’s educational concept, and how can it be applied? Accordingly, the study aims to explore al-Ghazālī’s educational philosophy and its relevance to contemporary moral challenges. The methodology applied is a library-based inductive approach, gathering primary sources—particularly Ayyuhā al-Walad—along with secondary references. The data were analyzed using a descriptive method to examine the phenomenon as it is and to provide a systematic interpretation. The findings reveal that al-Ghazālī emphasizes moral and spiritual education as the core of human development, advocating for self-discipline, sincerity, and the integration of knowledge with action. This research contributes to the broader discourse on moral education by presenting al-Ghazālī’s ideas as a timeless framework for addressing ethical decay in modern education, offering practical insights for educators and policymakers seeking to foster values-based learning.